Sepsis Diagnostics in the Era of "Omics" Technologies - Průcha, Miroslav; Zazula, Roman; Russwurm, Stefan (Prague medical report, 2018)
Sepsis is a multifactorial clinical syndrome with an extremely dynamic clinical course and with high diverse clinical phenotype. Early diagnosis is crucial for the final clinical outcome. Previous studies have not identified a biomarker for the diagnosis of sepsis which would have sufficient sensitivity and specificity. Identification of the infectious agents or the use of molecular biology, next gene sequencing, has not brought significant benefit for the patient in terms of early diagnosis. Therefore, we are currently searching for biomarkers, through "omics" technologies with sufficient diagnostic specificity and sensitivity, able to predict the clinical course of the disease and the patient response to therapy. Current progress in the use of systems biology technologies brings us hope that by using big data from clinical trials such biomarkers will be found.
Keywords: Communicable Diseases; Pharmacogenomics; systémová biologie; biologické markery; kritický stav; Biomarkers; sepse; Sepsis; Genomics; Systems Biology; lidé; proteomika; Metabolomics; infekční nemoci; Proteomics; Diagnostics; Proteinomics; Transcriptomics; Critical Illness; genomika; Humans